The heart of a woman - Angelou, Maya (New York Random House Trade Paperbacks, 2009)
In The Heart of a Woman, Maya Angelou leaves California with her son, Guy, to move to New York. There she enters the society and world of black artists and writers, reads her work at the Harlem Writers Guild, and begins to take part in the struggle of black Americans for their rightful place in the world. In the meantime, her personal life takes an unexpected turn. She leaves the bail bondsman she was intending to marry after falling in love with a South African freedom fighter, travels with him to London and Cairo, where she discovers new opportunities. The Heart of a Woman is filled with unforgettable vignettes of such renowned people as Billie Holiday and Malcom X, but perhaps most importantly chronicles the joys and the burdens of a black mother in America and how the son she has cherished so intensely and worked for so devotedly finally grows to be a man
Autobiography
Keywords: Angelou, Maya; African American women authors -- 20th century -- Biography; Authors, American -- 20th century -- Biography; Entertainers -- United States -- Biography